Tim-4 in Health and Disease: Friend or Foe? - Liu, Wen; Xu, Liyun; Liang, Xiaohong; Liu, Xiaojun; Zhao, Yangbing; Ma, Chunhong; Gao, Lifen (Frontiers in Immunology, 2020)
T-cell immunoglobulin and mucin domain containing 4 (Tim-4) is a phosphatidylserine receptor and is selectively expressed on antigen presenting cells. Recently, Tim-4 was reported to be expressed on iNKT cells, B1 cells, and tumor cells, suggesting it has multiple biological functions. In this review, we mainly summarize the expression and regulation of Tim-4 in immune cells including T cells, macrophages, dendritic cells, NKT cells, B cells and mast cells. The expression of Tim-4 in these cells implies that Tim-4 might participate in immune related diseases. Emerging evidence emphasizes a substantial role for Tim-4 in maintaining homeostasis by regulating various immune responses, including viral infection, allergy, autoimmunity and tumor immunity. Here, we collectively evaluated the role of Tim-4 in health and disease. This summary will be extremely useful to fully understand the function of Tim-4 in the pathogenesis of immune related diseases, which would provide novel clues for the diagnosis and treatment of diseases.